Chronic rhinosinusitis in asthma is a negative predictor of quality of life: results from the Swedish GA2LEN survey. Issue 10 (21st September 2013) - Ek, A.; Middelveld, R. J. M.; Bertilsson, H.; Bjerg, A.; Ekerljung, L.; Malinovschi, A.; Stjärne, P.; Larsson, K.; Dahlén, S.‐E.; Janson, C.
Abstract Background Asthma and chronic rhinosinusitis (CRS) both impair quality of life, but the quality‐of‐life impact of comorbid asthma and CRS is poorly known. The aim of this study was to evaluate the impact of CRS and other relevant factors on quality of life in asthmatic subjects. Methods This Swedish cohort (age 17–76 years) consists of 605 well‐characterized asthmatics with and without CRS, 110 individuals with CRS only, and 226 controls and is part of the Global Allergy and Asthma European Network (GA2LEN) survey. The Mini Asthma Quality of Life Questionnaire (mAQLQ), the Euro Quality of Life (EQ‐5D) health questionnaire, spirometry, skin prick test (SPT), exhaled nitric oxide (FeNO), smell test, and peak nasal inspiratory flow were used. Results Subjects having both asthma and CRS have lower mAQLQ scores in all domains (P < 0.001) and a lower EQ‐5D index value and EQ‐5D VAS value (P < 0.001) compared to those with asthma only. Asthmatics with CRS have significantly lower FEV1%pred and FVC%pred (88.4 [85.1–91.7] and 99.9 [96.7–103.0], respectively) compared with asthma only (91.9 [90.3–93.4] and 104.0 [102.5–105.5], respectively P < 0.05). Multiple regression analysis shows that low asthma quality of life is associated with having CRS (P < 0.0001), lower lung function (P = 0.008), current smoking (P = 0.01), BMI > 30 kg/m2 (P = 0.04), high age (P = 0.03), and a negative SPT (P = 0.04). Conclusions Comorbid CRS was a significant and independent negative predictor of quality of life in asthmatics. Other negative factors were lower lung function, current smoking, obesity, advanced age, and having nonatopic asthma.